Language profiles and literacy outcomes of children with resolving, emerging, or persisting language impairments. (17th December 2015) - Snowling, Margaret J.; Duff, Fiona J.; Nash, Hannah M.; Hulme, Charles
Abstract : Background: Children with language impairment (LI) show heterogeneity in development. We tracked children from pre‐school to middle childhood to characterize three developmental trajectories: resolving, persisting and emerging LI. Methods: We analyzed data from children identified as having preschool LI, or being at family risk of dyslexia, together with typically developing controls at three time points: t1 (age 3;09), t3 (5;08) and t5 (8;01). Language measures are reported at t1, t3 and t5, and literacy abilities at t3 and t5. A research diagnosis of LI (irrespective of recruitment group) was validated at t1 by a composite language score derived from measures of receptive and expressive grammar and vocabulary; a score falling 1 SD below the mean of the typical language group on comparable measures at t3 and t5 was used to determine whether a child had LI at later time points and then to classify LIs as resolving, persisting or emerging. Results: Persisting preschool LIs were more severe and pervasive than resolving LIs. Language and literacy outcomes were relatively poor for those with persisting LI, and relatively good for those with resolving LI. A significant proportion of children with average language abilities in preschool had LIs that emerged in middle childhood – a high proportion of these children were at family risk of dyslexia. There were more boys in the persisting and resolving LI groups. Children with early LIs which resolved by the start of formal literacy instruction tended to have good literacy outcomes; children with late‐emerging difficulties that persisted developed reading difficulties. Conclusions: Children with late‐emerging LI are relatively common and are hard to detect in the preschool years. Our findings show that children whose LIs persist to the point of formal literacy instruction frequently experience reading difficulties.